Evolution of the upper critical field and superconducting vortex phase with thickness in PLD-grown Ta films. (1st May 2022) - Liu, Yixin; Zhang, Han; Han, Xiaowen; Wang, Teng; Wang, Lingling; Niu, Zhengqi; Pan, Jie; Lin, Zhirong; Peng, Wei; Li, Zhuojun; Mu, Gang; Di, Zengfeng; et al.
Abstract: High quality superconducting thin films are the basis for the application of superconducting devices. Here, we report on the film growth and superconducting properties of Ta films. The films were grown by the pulsed laser deposition technique on the α -Al2 O3 substrates. It is found that, with the increase of the film thickness from 20 nm to 61 nm, both the superconducting transition temperature T c and residual resistance ratio (RRR) display an upward trend, while the upper critical field decreases monotonously in a wide temperature region. A clear anisotropic behavior is revealed by comparing the upper critical fields with two different orientations ( H ⊥ film and H ∥ film ). The anisotropy parameter Γ is found to be as high as 20 for the sample with the thickness of 20 nm. The systematical evolution from two- to three-dimensional features for the superconductivity with increasing the film thickness is observed in the temperature dependent upper critical field data. Moreover, the vortex liquid region tends to expand with the increase in the film thickness.